MANAGEMENT OF THE EXCELLENT CLASS OF INTERPRETATION AND AQIDA FOR ULAMA CADRES IN DAYAH ACEH - Hasnawi; Saifuddin; Haryuni; Januar Pandapotan; Ismawati; Iskandar; Najmuddin (STMIK Indonesia Banda Aceh, 2026)
Dayah as a traditional Islamic educational institution in Aceh has a strategic role in forming cadres of religious scholars who are competent in religious sciences, especially the sciences of tafsir and aqidah. In its development, there is a need to manage learning effectively through superior classroom management so that student coaching runs more optimally and is directed according to the goals of Islamic education. This study aims to describe the curriculum of tafsir and aqidah education in Aceh dayah, analyze the implementation of superior classroom management in tafsir and aqidah learning, and explain the relationship between tafsir and aqidah education in forming scholarly competence. This research uses a qualitative approach with literature study and document analysis methods. The results show that the tafsir and aqidah education curriculum in Aceh dayah is still tied to classical books (turats) such as Tafsir Jalalain, Aqidah al-Nasafiyah, and Jawharat al-Tauhid, but has undergone modernization through the tahqiq system and mufradat analysis. The application of superior classroom management includes the selection of high-achieving student inputs, intensive learning processes with discussion and mudzakarah methods, and output supervision in the form of scholarly competence with broad insight. The integration of tafsir and aqidah creates scholars who not only understand the content of the Qur'an but also have a straight and argumentative creed in accordance with the manhaj of Ahlussunnah wal Jama'ah..